Tác động của trải nghiệm thương hiệu đến quan hệ thương hiệu Ứng dụng cho ngành bán lẻ - Phạm Thị Lan , Hương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study aims to measure the impact of brand experience on brand relationship. The content of the argument refers to brand experience, the nexus between brand experience and brand relationship, and patterns or scales of brand experience in the retail service. Data are collected by means of direct personal interviews with 260 consumers aged from 18 to 55, shopping at retail supermarkets, such as Big C, Co.op Mart, and Lotte Mart in Danang. The research results show the positive impacts of brand experience components on brand personality, brand trust, and brand satisfaction besides the positive effects of brand experience and brand satisfaction on brand commitment and brand community or the impacts of brand experience and satisfaction on brand loyalty. No effects are found of sense of community and brand commitment on brand loyalty. The study contributes theoretically to the synthesis of the scales of brand experience and practically to the formulation of marketing strategies for retail stores in Vietnam.